The power of public choice in law and economics - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
In this paper I discuss how Law and Economics can benefit from incorporating some insights from Public Choice into their analyses. Within this argument, I examine the evolution of experimental methods by looking at laboratory, field, and natural experiments; and conducting a very simple scientometrics analysis on the relative frequency of experimental studies in journals such as Public Choice, Journal of Law and Economics, and Journal of Law, Economics and Organization in comparison to top economics journals such as American Economic Review, Quarterly Journal of Economics, Journal of Political Economy, Econometrica, or Review of Economic Studies. I also refer to the connectivity of Behavioral Law and Economics and Behavioral Public Choice. The paper then finishes with a discussion of a selected number of topics covering areas such as corruption, tax compliance, shitstorms/firestorms, constitutional choices, globalization and international organizations; all of which present scientific challenges when applying pure Law and Economics approaches without also implementing a Public Choice analysis.
Keywords: 330